2015
DOI: 10.1051/0004-6361/201423788
|View full text |Cite
|
Sign up to set email alerts
|

Galactic cold cores

Abstract: Context. The project Galactic Cold Cores has carried out Herschel photometric observations of interstellar clouds where the Planck satellite survey has located cold and compact clumps. The sources represent different stages of cloud evolution from starless clumps to protostellar cores and are located in different Galactic environments. Aims. We examine this sample of 116 Herschel fields to estimate the submillimetre dust opacity and to search for variations that might be attributed to the evolutionary stage of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 106 publications
(126 reference statements)
1
68
1
Order By: Relevance
“…Planck Collaboration XXV (2011) examined the Taurus region and found β > 1.8 in structures with temperatures below 14 K. Juvela et al (2012) used an average value of 2 when determining the T dust and N(H 2 ) on the fields observed during the Herschel open time key programme Galactic Cold Cores. Recently Juvela et al (2015b) examined the sub-millimeter dust opacity and gave the average value of β close to 1.9 and they indicated that it can be even higher in the coldest regions. The variations of β were described in detail by Juvela et al (2015a).…”
Section: A1 Determination Of the Background Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Planck Collaboration XXV (2011) examined the Taurus region and found β > 1.8 in structures with temperatures below 14 K. Juvela et al (2012) used an average value of 2 when determining the T dust and N(H 2 ) on the fields observed during the Herschel open time key programme Galactic Cold Cores. Recently Juvela et al (2015b) examined the sub-millimeter dust opacity and gave the average value of β close to 1.9 and they indicated that it can be even higher in the coldest regions. The variations of β were described in detail by Juvela et al (2015a).…”
Section: A1 Determination Of the Background Levelmentioning
confidence: 99%
“…We fitted the spectral energy distribution (SED) of each pixel with B ν (T dust )ν β , where B ν (T ) is the Planck-function for a black body with colour temperature T dust at ν frequency. The value of β varies between 1.8 to 2.2 in the cold dense interstellar medium (ISM) anti-correlates with temperature and correlates with column density and galactic position (Juvela et al 2015b); see Appendix A.2 for further information. In our calculations the SED was fitted to all three SPIRE data points with a fixed β = 2 spectral index and returned T dust for each pixel.…”
Section: Calculations From Herschel Spire Datamentioning
confidence: 99%
“…The lower limit rather represents non-coagulated dust in diffuse clouds so that it is probably not representative for Rosette. For Planck cold cores Juvela et al (2015) estimated 1.5 × 10 −25 cm 2 /H when converted to 300 µm. Taking this range, we estimate that the dust emissivity has an accuracy of 30 − 50%.…”
Section: Molecular-line and Dust Emission Mapsmentioning
confidence: 99%
“…To study the variations in the submillimetre dust opacity, Juvela et al (2015b) compared the 250 µm optical depths to the near-infrared (NIR) extinctions. The typical value of τ(250µm)/τ(J) in the fields was found to be 1.6 × 10 −3 , which is more than twice the values in diffuse medium (Planck Collaboration et al 2014a,b) but consistent with other Planck studies of molecular clouds (Planck Collaboration et al 2014c) (see also, e.g.…”
Section: Introductionmentioning
confidence: 99%